PROSES STAMPING PART BRACKET LEVER SELECT CABLE MENGGUNAKAN MESIN STAMPING PRESS MEKANIK - Aditya, Dadang; Koswara , Engkos (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
This report contains the Stamping process carried out on the Part Bracket Lever Select Cable. The Stamping process is a process of forming metal/iron material coldly using dies and a press machine on the printed material to produce products according to plan. One of the main components when carrying out the Stamping process is Dies. Dies are objects used in the industrial world to print objects with the help of a Press machine to press the workpiece. When setting the Dies, we must also determine the appropriate Die Height. Therefore, the purpose of this report is to choose the appropriate Dies for the Part Bracket Lever Select Cable Stamping process and what Die Height value is used. The stages taken to carry out the Part Bracket Lever Select Cable Stamping process are the Planning process, material preparation, Dies Setting, the Stamping process which includes the Pierching, Blanking and Restrike processes, and Inspection. In carrying out the Part Bracket Lever Select Cable Stamping process, Progressive Dies are used for the Pierching and Blanking processes, while for the Restrike process, Single Station Dies are used. While the Die Height is set at 350 mm.